COVID-19 and Cerebrovascular Diseases: A Systematic Review and Perspectives for Stroke Management - Fraiman, Pedro; Godeiro Junior, Clecio; Moro, Elena; Cavallieri, Francesco; Zedde, Marialuisa (Frontiers in Neurology, 2020)
The clinical syndrome of COVID-19 infection is complex and implies multiorgan involvement. It has become evident that neurological manifestations of COVID-19 are not rare and can involve both the central and peripheral nervous system. In a patient with confirmed or suspect COVID-19 infection, any acute neurologic symptoms, especially cerebrovascular related, should be considered a potential COVID-19 neurological complication. Reported cerebrovascular events in patients with COVID-19 are mainly ischemic, but also hemorrhagic strokes and cerebral venous thrombosis, especially in critically ill patients, have been described. To date, it is still not clear whether cerebrovascular manifestations are caused by the direct viral action or an indirect action mediated by inflammatory hyperactivation. This review focuses on clinical and etiological presentation of stroke in COVID-19 patients with the aim at increasing knowledge and improving care of this frequent neurological event.